GENETIC PARAMETER ESTIMATES FOR PRODUCTION AND REPRODUCTION TRAITS IN DAIRY BUFFALOES - Barros, Camila Da Costa [UNESP]; Aspilcueta-Borquis, Rusbel Raul; Fraga, Angelina Bossi; Tonhati, Humberto [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2016)
The objective of this study was to determine the genetic variation in milk production, milk components, and reproductive traits in dairy buffaloes. A total of 9,318 lactation records from 3,061 cows were used to estimate the heritability of milk yield (MY), fat percentage (% F), protein percentage (% P), lactation length (LL), calving interval (CI), and age at first calving (AFC), as well as genetic and phenotypic correlations between these traits. Covariance components were estimated by Bayesian inference in a multitrait animal model using the GIBBS2F90 program. Contemporary groups and number of milkings (1 or 2) were included as fixed effects, age of dam at calving (linear and quadratic effects) as a covariate, and additive genetic, permanent environmental, and residual effects as random effects. The heritability estimates (+/- standard deviation) were 0.24 +/- 0.02, 0.34 +/- 0.05, 0.40 +/- 0.05, 0.09 +/- 0.01, 0.05 +/- 0.01, and 0.16 +/- 0.04 for MY, % F, % P, LL, CI, and AFC, respectively. The genetic correlations between MY and % F, % P, LL, CI, and AFC were -0.29, -0.18, 0.66, 0.08, and 0.24, respectively. Milk production and milk components showed sufficient genetic variation to obtain genetic gains through selection. The genetic correlations between MY and milk components were negative, and thus, undesirable because efforts to increase MY may decrease milk quality. Reproductive traits had little genetic influence, indicating that improvement of management would be sufficient to obtain better performance.
Keywords: Buffalo; Genetic correlation; Heritability; Milk yield